Efficacy of 308-nm excimer laser combined with fractional CO2 laser in treatment of stable vitiligo - Ya-nan KE; Yong YU; Xiu-ling SHEN; Kun-xia YANG; Ya-ping TANG; Zhen-jie LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To evaluate the efficacy and safety of fractional CO2 laser combined with 308-nm excimer laser for the treatment of stable vitiligo. Methods: A total of 118 patients of stable vitiligo were enrolled in this trial. Patients were assigned into the treatment group (n=59, 328 lesions) and control group (n=59, 319 lesions) using a random digital table method. The treatment group was treated with fractional CO2 laser combined with 308-nm excimer laser, while the control group was treated with 308-nm excimer laser alone. Efficacy and adverse reactions were evaluated after 3 months of consecutive treatments. Results: After the treatments, the total effective rates were higher in the treatment group than that in the control group (89.94% vs. 84.64%, χ2=6.59, P=0.014). The rate of the adverse reactions did not differ between the two groups (23.34% vs. 22.15%, χ2=1.29, P=0.088). Conclusion: 308-nm excimer laser combined with fractional CO2 laser is safe and effective for patients with stable vitiligo.